PEMBINAAN KEPRIBADIAN DALAM PEMBELAJARAN BAHASA ARAB MELALUI KITAB AQIDATUL AWAM DI TPQ RAUDLATUL SHIBYAN - Ghofur, M Abdul; Abdul Jalil Mannan, Ahmad Mizan Rosyadi; Mustafida, Agustina Farchiyatul (INAIFAS Press, 2025)
Personality development activities in learning Arabic through the aqidatul lay book for beginner TPQ Raudlatul Shibyan students which focuses on developing honesty, politeness, sincerity and responsibility which are still low at the age of TPQ students who are still beginners. The aim of this research is to develop the moral personality of al-karimah in learning Arabic so that they are able to improve their behavior and also increase their knowledge about the science of monotheism through learning the lay aqidatul book. The method used is the method of teaching and providing direct examples and providing motivation. Meanwhile, data collection techniques use observation, interviews and documentation. The results obtained from the development went well and the desired changes received a fairly high percentage.Keywords: Development, Personality, The Aqidatul lay book.